Recursos didácticos en el área de la matemática y su incidencia en la profesionalización del docente de educación general básica, año 2014 - Contreras Oña, Jenny Alexandra (2015)
The thesis presented addresses a current problem and socio educative according the shortcomings in the use of didactic resources into the teaching and learning process of Math in General Basic Education, as an alternative solution to the scientific problem posed is developed a methodological guide for the use of educational resources for teaching and learning of mathematics in General Basic Education; the results obtained ofapplying the methodsanalytic-synthetic, hypothetical-deductive, modeling and empirical methods, substantiate that the proposal is appropriate and feasible in correspondence to the purposes for which it is created.